Dynamic online antimicrobial guideline with stewardship program: Impact on antimicrobial prescribing - Sultana, Syeda Papia; Rahman, Md. Sayedur (Bangladesh Journal of Pharmacology, 2017)
Dynamic online antimicrobial guideline with stewardship program was attempted in Bangabandhu Sheikh Mujib Medical University (BSMMU) to improve the antimicrobial prescribing. The prescribing pattern was evaluated by retrospective prescription audit. Overall 59.4% of admitted patients of four selected departments received antimicrobials. Highest (81.9%) was in the Department of Obstetrics and Gynecology, followed by Surgery (78.5%), Internal Medicine (47.6%) and Pediatrics (46.7%). After launching of guideline, antimicrobial prescribing was significantly reduced in the Department of Internal Medicine (47.6% to 22.2%; p<0.01) and Pediatrics (50.0% to 40.0%; p<0.01). Significant (p<0.05 to p<0.001) change was observed with different antimicrobials in different departments. Consumption of cefixime (8.5 ± 3.7 to 3.9 ± 2.5; p<0.05) and ceftriaxone (6.9 ± 3.4 to 3.1 ± 2.2; p<0.005) was reduced significantly in Internal Medicine. The adherence to guideline was highest in the Department of Obstetrics and Gynecology (91.3%) followed by Pediatrics (86.3%) and Internal Medicine (81.2%).